Análisis del proceso metodológico en la formación de base en los futbolistas de las categorías inferiores de Liga Deportiva Cantonal de Catamayo - Peñafiel Labanda, Frank Manuel (2014)
This research topic methodological analysis in forming process based on the players in the lower levels of cantonal Catamayenses sports league . The problem is How it affects the methodological process in forming the basis of the players that coaches use the lower echelons of sports league Catamayenses cantonal and As in all central problem situations that are implicit in them is derived ; therefore derived some problems as not having the impact the coach knows and exercises on the player base focused on their training or performance identified ; Planning made by coaches, is not centered on the formation of the players and coaches basic lack of training not geared towards sport training base in the players of the training categories. It aims to achieve the overall objective methodological know how this affects the formation process based on the players in the lower levels of cantonal sports league Catamayo.Los main methods that support this research were scientific method ; Analytical Method Synthetic heuristic method ; The statistical method Deductive and Inductive Method . . Techniques applied were The Observation Guide - This technique is used for close observation of the facts and phenomena ; Poll - . Technique is also called the questionnaire and interview . - This instrument will be applied to athletes to gather information to know how it affects the methodological process . The investigated population was established by 2 coaches and 60 athletes. Among the most significant results came to the conclusion that : For the teaching of football in the Liga Deportiva Cantonal Catamayenses the methods used are not as suitable for teaching soccer in lower category because students do not understand well and not not fully exploit the skills to discipline ; Planning made by coaches, is focused on the formation of the same players that do not specifically know the planning done by the coach.